KENDALIKAN TEKANAN DARAH PADA LANSIA DENGAN TERAPI KOMPLEMENTER - Purqoti, Dewi Nur Sukma; Istiana, Dian; Arifin, Zaenal; Pramudita, Eka Avina (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2024)
Non-Communicable Diseases (NCDs) often referred to as NCDs have become a considerable public health problem in Indonesia, this is marked by a shift in epidemiological disease patterns from infectious diseases to NCDs which globally continues to increase, one of which is hypertension. The purpose of this study is to determine the effect of complementary therapy on lowering blood pressure in the elderly with hypertension. This research method is pre-experimental with a one-group pre-post test design. The population in this study is 152 people with a sample of 18 respondents, Sampling with non-probability sampling techniques, The instrument that will be used in this study is a data processing questionnaire using the wilcoxon test. The results showed that the Sig (2-tailed) value for systolic blood pressure before and after the administration of complementary therapy was 0.000 < 0.05 its means that Ha is accepted and Ho is rejected. In conclusion, there is an effect of providing complementary therapy on reducing blood pressure in the elderly with hypertension